Long Non-coding RNAs LOC100126784 and POM121L9P Derived From Bone Marrow Mesenchymal Stem Cells Enhance Osteogenic Differentiation via the miR-503-5p/SORBS1 Axis - Xu, Yiyang; Xin, Ruobing; Sun, Hong; Long, Dianbo; Li, Zhiwen; Liao, Hongyi; Xue, Ting; Zhang, Ziji; Kang, Yan; Mao, Guping (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) play pivotal roles in mesenchymal stem cell differentiation. However, the mechanisms by which non-coding RNA (ncRNA) networks regulate osteogenic differentiation remain unclear. Therefore, our aim was to identify RNA-associated gene and transcript expression profiles during osteogenesis in bone marrow mesenchymal stem cells (BMSCs). Using transcriptome sequencing for differentially expressed ncRNAs and mRNAs between days 0 and 21 of osteogenic differentiation of BMSCs, we found that the microRNA (miRNA) miR-503-5p was significantly downregulated. However, the putative miR-503-5p target, sorbin and SH3 domain containing 1 (SORBS1), was significantly upregulated in osteogenesis. Moreover, through lncRNA-miRNA-mRNA interaction analyses and loss- and gain-of-function experiments, we discovered that the lncRNAs LOC100126784 and POM121L9P were abundant in the cytoplasm and enhanced BMSC osteogenesis by promoting SORBS1 expression. In contrast, miR-503-5p reversed this effect. Ago2 RNA-binding protein immunoprecipitation and dual-luciferase reporter assays further validated the direct binding of miR-503-5p to LOC100126784 and POM121L9P. Furthermore, SORBS1 knockdown suppressed early osteogenic differentiation in BMSCs, and co-transfection with SORBS1 small interfering RNAs counteracted the BMSCs’ osteogenic capacity promoted by LOC100126784- and POM121L9P-overexpressing lentivirus plasmids. Thus, the present study demonstrated that the lncRNAs LOC100126784 and POM121L9P facilitate the osteogenic differentiation of BMSCs via the miR-503-5p/SORBS1 axis, providing potential therapeutic targets for treating osteoporosis and bone defects.